Computational Biology - B Thiagarajan (MJP Publishers, 2009)
With more and more people depending upon interactive software applications, web applications, mobiles and other digital devices, this book gives the essence of computers and programming that would be useful for life scientists, as the first part. The topics in this part would suit the needs of the life scientists and this would lead them to learn more about the technical aspects of algorithms they come across in Bioinformatics, once they find themselves masters in programming. The second part brings together leading-edge research from top scientists around the world, as well as beginners, who are not exposed to the biological areas of systems biology. This part deals with all essential concepts in the creation of plasmid, restriction site analysis, EST, microarray, basic concepts in genomics and the databases such as KEGG, MGRC, analysing comparative studies on VISTA server, and so on. This book would prove helpful for readers to get a basic idea of computational biology.